Ten Young Artists - Theodoron Awards. (New York : The Solomon R. Guggenheim Foundation, 1971)
Boothe, Power ; Cooper, Ron ; Bryant Copley, Billy ; Corse, Mary ; Dill, Guy ; Gerndt, Andrew ; Korman, Harriet ; Nelson, Dona ; Singer, Michael ; Trakas, George
Ten Young Artists - Theodoron Awards, The Solomon R. Guggenheim Museum, New York, 1971
boek